NEW CONTRIBUTIONS TO VEGETATION KNOWLEDGE OF THE DANUBE DELTA, ROMANIA (I) - Adrian OPREA; Culiţă SÎRBU; Mihai DOROFTEI; Silviu COVALIOV (Journal of Plant Development)
New investigations on the flora, vegetation, and natural habitats of the Danube Delta (Romania) were recently carried out. Thus, more than 1,200 vascular plant species were inventoried, phytocoenoses of 253 plant communities, and 32 Natura 2000 habitats were recorded, all mapped on a large scale. As part of the reviewing process of the Standard Form of the Natura 2000 site ROSCI0065 Danube Delta - Romania, the natural habitats included within it were also revised. Thus, it was found that black alder forests were omitted, which was one the purposes of this work, namely to fill this gap. Following the recordings of all black alder forests in the Danube Delta, a phytocoenotaxon is proposed as new for science, namely Ass. Periploco graecae-Alnetum glutinosae ass. nov. The Natura 2000 habitat in the Danube Delta that include this newly proposed plant community is: 91E0* Alluvial forests with Alnus glutinosa and Fraxinus excelsior (Alno-Padion, Alnion incanae, Salicion albae).